Beamforming design with partially adaptive and minimum redundancy arrays - Presti, L.L.; Montalbano, G.; Povero, G. (1996 IEEE International Conference on Acoustics, Speech, and Signal Processing Conference Proceedings, 1996)
This paper proposes a beamforming design method for interference cancellation using a special thinned array structure, termed minimum redundancy array (MRA). MRA is analyzed with partially adaptive beamforming design techniques and compared with corresponding uniform regular array (URA) over a set of likely interference scenarios. The partially adaptive beamformer design is subject to worst-case performance constraints. Extensive numerical simulations with several sets of interference scenarios show that MRA almost always outperforms URA, in both cases of fully adaptive beamformers and of partially adaptive beamformers. We also introduce a design criterion to take into account both the array geometry and partially adaptive beamforming methods.